Challenges, Innovations, and Future Directions in Life Cycle Assessment of Product and Process Impacts - Nicolás Martín Clauser; Maria Cristina Area (BioResources, 2025)
Reliable estimation of the environmental impacts of processes and products is essential for achieving the Sustainable Development Goals. Life cycle assessment (LCA) is a key method for evaluating such effects. Since its development, the concept has evolved to improve the precision of the obtained results. In addition to software tools, various focuses are available that consider factors such as sustainability, social aspects, and organizational perspectives. Beyond the advancements made, there is still a need for improvement in developing accurate models and frameworks. In this sense, developments such as new information technologies can be key players in the field.